THE ROLE OF BRICS IN ESTABLISHING THE BALANCE OF POWER IN INTERNATIONAL RELATIONS - Proroković, Dušan (Serbian political thought, 2024)
At the summit in Johannesburg in August 2023, BRICS members made a decision on expansion, and an invitation for full membership was sent to the addresses of six more potential members. A year before, an agreement was reached on the establishment of a reserve basket of currencies, the first step in the creation of an international reserve currency. The obvious goal is to create alternative financial institutions in opposition to the IMF, the World Bank and the WTO and to reduce the political influence of the USA and the collective West by de-dollarizing the global economy. This paper proves the thesis that BRICS was created due to the establishment of a balance of power in international relations. That is, that the decisions that are made are motivated by the political reasons for which this platform was founded. Therefore, the balance of power is not established due to de-dollarization, but de-dollarization is purposefully induced in order to achieve the balance of power in international relations. Or, the expansion of BRICS is not due to a change in the balance of power, but the expansion of BRICS accelerates the establishment of a new balance in international relations. The intensification of integrations within BRICS, as well as the intensification of strategic BRICS projects, such as the establishment of the New Development Bank and the announcement of de-dollarization, were influenced by two important events in the last decade and a half: the Arab Spring and the escalation of the Ukrainian crisis. Changes in international relations and the security environment forced BRICS to speed up the development of specific projects and their implementation. As a result, the establishment of the balance of power is taking place faster than previously predicted.
Keywords: BRICS; collective West; de-dolarization; New Development Bank; balance of power